Philippine Economic Update, October 2015 : Making Growth Work Better for Small Businesses - World Bank (Washington, DC, 2015)
The Philippines is among the strongest performers in the region, bucking the trend. In the first half (H1) of 2015, among the major economies in the region, the only countries to accelerate their quarterly growth rates were the Philippines, from 5 to 5.6 percent, and Vietnam. In spite of this acceleration, for the two quarters combined, Philippine growth rate came out at 5.3 percent—its lowest half year growth rate since 2011. On the demand side, the strong performance of private domestic demand at 8.1 percent, supported by record low inflation and robust remittances, drove GDP growth. However, the slow pace of public spending and the contraction in net exports pulled down GDP growth. On the supply side, the onset of El Niño led to stagnant agriculture growth. Meanwhile, growth in industry and services was respectable, with both sectors growing by around 5.8 percent. In Q3, available high frequency data suggest an improving economy, in particular, an acceleration in government spending.